An assessment of the public attitudes towards the inner City of Johannesburg as a branded destination - Daya, Nikita JC; Chiliya, N (My University, 2014)
Cities across the world have shifted their focus to urban development and place marketing strategies. These concepts are increasingly becoming important since the competition between cities have intensified globally in order to obtain investments, attract tourists, provide better living space, and to improve community businesses and overall economies of the city. Johannesburg has made use of various labels to provide a unique and attractive destination brand. The city has undergone significant changes in order to improve and reposition its image. In particular, there has been a focus on the redevelopment and brand image repositioning of the Inner City of Johannesburg. Redevelopment strategies have been outlined and implemented in order to improve the areas within the Inner City of Johannesburg. The primary purpose of this study was to investigate the effects of the current attitudes and perceptions of the public towards the Inner City of Johannesburg. A quantitative approach was used. A convenience sample consisting of 343 individuals within the Inner City of Johannesburg completed the distributed survey instrument. The data analysis consists of multiple linear regression analysis. The results of this study indicate that Government services and social bonding are the key factors the public value when they visit the inner city.
Keywords: Place branding; Branded Destination; Attitudes